2019
DOI: 10.7150/thno.37198
|View full text |Cite
|
Sign up to set email alerts
|

Alliance with EPR Effect: Combined Strategies to Improve the EPR Effect in the Tumor Microenvironment

Abstract: The use of nanomedicine for cancer treatment takes advantage of its preferential accumulation in tumors owing to the enhanced permeability and retention (EPR) effect. The development of cancer nanomedicine has promised highly effective treatment options unprecedented by standard therapeutics. However, the therapeutic efficacy of passively targeted nanomedicine is not always satisfactory because it is largely influenced by the heterogeneity of the intensity of the EPR effect exhibited within a tumor, at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
180
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(197 citation statements)
references
References 144 publications
(157 reference statements)
4
180
0
Order By: Relevance
“…However, clinical studies demonstrated that compared to murine experimental tumors the EPR level in human tumors was less pronounced and could differ substantially not only between the same type tumors in different patients, but also between various sites of metastasis in a single patient [156]. In attempts to overcome instability of nanoparti cles it was suggested to make them functionally addressed by, for example, attaching EGFR specific ligands [157,158].…”
Section: The Use Of Egfr As a Delivery Systemmentioning
confidence: 99%
“…However, clinical studies demonstrated that compared to murine experimental tumors the EPR level in human tumors was less pronounced and could differ substantially not only between the same type tumors in different patients, but also between various sites of metastasis in a single patient [156]. In attempts to overcome instability of nanoparti cles it was suggested to make them functionally addressed by, for example, attaching EGFR specific ligands [157,158].…”
Section: The Use Of Egfr As a Delivery Systemmentioning
confidence: 99%
“…or internal (pH, enzymatic, redox, etc.) stimulus to produce the local release of the drug [7,8]. In particular, pH has been used for a long time as a critical feature for the differentiation between healthy tissues and abnormal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid (HA) terminal groups were attached to PAMAM core through PLGLAG peptide linkages, which can be cleaved by MMP-2 at tumor sites, and the dendrimer will shrink from ~200 to ~10 nm. The size shrinkage property benefits the cleaved dendrimers in the enhanced permeability and retention (EPR) effect, thus improving the cellular uptake of nanoparticles [ 132 , 133 ]. Liu et al also employed MMP2-sensitive peptide (GPLGIAGQ) in generation 4 PAMAM dendrimers for delivering cytotoxic peptide KLAK [ 118 ].…”
Section: Dendrimersmentioning
confidence: 99%